2015
DOI: 10.1111/1751-2980.12251
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic prediction of tumor margin and invasive depth in early gastric cancer

Abstract: Gastric cancer (GC) is the fifth most common cancer and the third leading cause of cancer-related deaths in the world. The prognosis of GC is clearly associated with the tumor stage, with a 5-year overall survival rate for early gastric cancer (EGC) exceeding 90%, which is significantly higher than that of advanced gastric cancer. Endoscopic resection, including endoscopic mucosal resection and endoscopic submucosal dissection, has been adopted in recent decades as the first treatment option of EGC in many cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Of course, the classification of pathological tumors is valuable in predicting the prognosis of patients with gastric cancer. Many studies have found some independent prognostic factors in tumor-related factors of gastric cancer, such as lymph node status, tumor invasion depth, and molecular markers [12][13][14]. However, these prognostic factors are not present at the time of gastrectomy or when tissue is not available, as they are largely dependent on histological examination of the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the classification of pathological tumors is valuable in predicting the prognosis of patients with gastric cancer. Many studies have found some independent prognostic factors in tumor-related factors of gastric cancer, such as lymph node status, tumor invasion depth, and molecular markers [12][13][14]. However, these prognostic factors are not present at the time of gastrectomy or when tissue is not available, as they are largely dependent on histological examination of the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…In current clinical practice, the tumor invasion depth is predicted based on macroscopic features using conventional endoscopy or endoscopic ultrasonography (EUS). With conventional endoscopy, various morphological features have been reported as predictors of the tumor invasion depth [ 30 ]. Reported indicators of EGC deeper than SM1 observed with WLI include pathomorphological changes at the tips of converging folds, a tumor diameter greater than 30 mm, marked erythema, surface irregularities, marginal elevation with and without submucosal tumor-like features, and trapezoid elevation [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Computed tomography, magnetic resonance imaging, and positron emission tomography are mainly used to evaluate advanced gastric cancer, but these methods are not accurate in predicting the infiltration depth of EGC (3). Currently, judgement of the infiltration depth of mucosal neoplastic lesions relies on white-light endoscopy (WLE), magnifying endoscopy with narrow-band imaging (ME-NBI), and endoscopic ultrasonography (EUS); however, each approach has its limitations (4). Until now, there has been no consensus regarding the need for preoperative EUS.…”
Section: Introductionmentioning
confidence: 99%
“…Whether EGC can be treated endoscopically depends mainly on the risk of lymph node metastasis, which correlates with the invasion depth of the tumor (1). Therefore, accurate prediction of the tumor invasion depth is of great importance in planning an appropriate treatment strategy and promising curative resection (2). Computed tomography, magnetic resonance imaging, and positron emission tomography are mainly used to evaluate advanced gastric cancer, but these methods are not accurate in predicting the infiltration depth of EGC (3).…”
Section: Introductionmentioning
confidence: 99%